Tata Kelola Teknologi Dalam Perencanaan Sektor Publik - Yuliar, Sony (Journal of Regional and City Planning, 2008)
While in general planning concerns with social criteria and objectives, the implementation of planning often involves the introduction of new technology to regional/local communities. An important question for  successful  planning  implementation would  then  be  how  those  social criteria  and objectives  be integrated  into  technology  selection  process.  This  question  leads  us  to  a  technology governance/steering problem within the context of planning. This article addresses this problem within the context of public sector planning, by arguing for a socio-technical co-evolutionary approach. By employing the notion of translation that is central in actor-network theory, a model for empirical studies is proposed. Empirical cases are presented from which normative principles for technology governance in public sector planning can be drawn.